Electrocatalysts: Highly Efficient Non‐Precious Metal Electrocatalysts Prepared from One‐Pot Synthesized Zeolitic Imidazolate Frameworks (Adv. Mater. 7/2014). (February 2014) - Zhao, Dan; Shui, Jiang‐Lan; Grabstanowicz, Lauren R.; Chen, Chen; Commet, Sean M.; Xu, Tao; Lu, Jun; Liu, Di‐Jia
<x xml:space="preserve">Abstract</x> A method for the preparation of highly efficient, non‐precious metal electrocatalysts for the oxygen reduction reaction, through pyrolyzing one‐pot synthesized zeolitic imidazolate framework (ZIF) materials is reported by D.‐J. Liu and co‐workers on page 1093. Excellent current and power densities of the polymer electrolyte fuel cells are demonstrated using such catalysts as the cathode. This approach not only makes ZIF‐based electrocatalysts easy to scale up, but also paves a new way for studying the influence of different N‐containing ligands to the catalytic activity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>